Stimulasi Kemampuan Numerasi Anak Usia Dini Melalui Permainan Moka (Monopoli Angka) Di TK Bunga Tanjung - Novi Safitriana Risqi; Azzahra Balqis Hauro; Febriyanti Febriyanti; Mufida Nabila; Winda Sherly Utami; Rizki Surya Amanda (Journal on Education, 2024)
This study aims to describe how MOKA (Monopoly Numbers) learning media can stimulate early childhood numeracy skills. The research method used is a qualitative approach with participants totaling 11 early childhood at Bunga Tanjung Kindergarten who have participated in learning with MOKA media. Data collection techniques include observation, interviews, and documentation. The results showed that the MOKA game was effective in developing children's numeracy skills. Significant improvements were seen in recognizing number symbols, understanding number concepts, and following the rules of play from the first day to the third day of observation. In addition to helping in the development of numeracy skills, MOKA games also have an important role in teaching the concept of cooperation, patience in waiting for their turn, and discipline in following the rules of play. In conclusion, MOKA games can be an effective alternative learning media in stimulating early childhood numeracy development, strengthening understanding of number concepts, and improving their social interactions.